Analytical estimation of natural frequency in earth dams with respecting to the foundation effects - Navid Hasani; Ali Ghanbari; S.Ali Asghar Hosseini (Numerical Methods in Civil Engineering, 2014)
There are varieties of techniques for calculating natural frequency of the structures. Nevertheless, these equations are less developed in the geotechnical structures such as slopes, buttress group, dams, and retaining walls. In earth dams, with respecting to the dimensions and weight of dam, soil-structure interaction is of prime importance for finding seismic parameters including natural frequency, deformation, and other parameters. To accomplish this objective and the inclusion of foundation flexibility, dam foundation was simulated using transition spring. in this research an equation is presented for calculating natural frequency of earth dam using analytical methods. The advantages of this method include more accurate estimation of seismic parameters as well as considering the flexibility of earth dams' foundation. Riley approximation method and shear-free shape function were used in the mathematical solution steps and the trend of gaining the proposed equation. Finally, the results obtained from the proposed equation were compared to those of finite element software GeoStudio-2007[9] and the correlation of responses was observed.